Fragility fracture of talar neck in an osteoporotic patient treated by posterior-to-anterior screw fixation under hindfoot endoscopy: a case report. Issue 2 (2nd February 2023) - Morio, Futoshi; Morimoto, Shota; Tachibana, Toshiya; Iseki, Tomoya
Abstract: Fragility fractures of the talar neck are extremely rare. Here, we describe a case of fragility fracture of the talar neck associated with osteoporosis in a 76-year-old female, who was treated by posterior-to-anterior screw fixation under hindfoot endoscopy. A 76-year-old female cleaner with a history of osteoporosis complained of pain in her right ankle when going downstairs. Radiological findings revealed a fragility fracture of the talar neck associated with osteoporosis. Because the patient was elderly and it was difficult to treat using a prolonged non-weight-bearing cast, we performed a posterior-to-anterior parallel dual screw fixation under hindfoot endoscopy for this case. As a result, the patient was able to return to work 8 weeks after surgery without pain, dysfunction or complication. Osteosynthesis with posterior-to-anterior screw fixation under hindfoot endoscopy successfully treated a rare case of fragility fracture of the talar neck in a 76-year-old female cleaner.